No more Sabado nights (videorecording) - Magsanoc, Kara; Rimban,Luz (Quezon City PCIJ, 1996)
No more nights tells the story of how the women of Tawid Sapa, Novaliches, organized themselves against wife bating set up a refuge for battered women and even got the government to anstall electric lines and dig up wells in their community.
Copied from original copy VHS-000125
Keywords: Battered wives -- Philippines; Women -- Philippines; Women -- Tawid Sapa, Novaliches